Humanization in the process of working in nursing: a reflection - Fontana, Rosane Teresinha (Rev Rene, 2010)
This study has as objective to refl ect on the humanization of the process of work in the health area, having as a focus the nursing workers, considering that the National Politics of Humanization encourages the autonomy and the protagonism of the subjects who are health producers. The Ministry of Health documents were used as the main reference that regulates such Policies, being articulated to some primary sources of scientifi c inquiry concerning the subject. Some alternatives are pointed with respect to the humanization of the practice centered in the worker, admitting the commitment with the ambience and improvement of the work conditions. To establish solidarity and participatory bonds and to transform the management models, having as focus the democratization of the work relations and the valuation of the health professionals are attitudes that can add value to the human being.